Korelacije genskih polimorfizama angiotenzin-konvertujućeg enzima 2 sa početkom i prognozom hipertrofične kardiomiopatije: Gene Polymorphisms of ACE2 in Hypertrophic Cardiomyopathy Outcomes - Li, Sujuan; Lin, Xizhi; Ye, Haoting; Li, Biyun; Zeng, Siyu; Mei, Qinghua; Huang, Yukai; Liu, Yixuan (Journal of Medical Biochemistry, 2025)
Background: To investigate the correlations of the gene polymorphisms of angiotensin-converting enzyme 2 (ACE2) with the onset and prognosis of hypertrophic cardiomyopathy (HCM), so as to provide references for the early prevention and precise treatment of HCM in the future. Methods: In this case-control study, a total of 100 HCM patients (HCM group) and 100 healthy people receiving physical examination who had matched age, gender and race (Control group) were collected. The single nucleotide polymorphisms (rs102312, rs102883 and rs119247) in the promoter region of ACE2 gene were genotyped by means of conformation-difference gel electrophoresis. Whether the distribution frequency of ACE2 genotypes is in agreement with the law of genetic equilibrium was examined using chi-square test. Meanwhile, the correlations of different polymorphisms and alleles in the promoter region of ACE2 gene with the onset and prognosis of HCM were analyzed. Results: The Hardy-Weinberg equilibrium analysis showed that all the three polymorphisms of ACE2 gene were in agreement with the law of genetic equilibrium (p>0.05). According to the results of genetic association analysis, the polymorphism rs102312 and its alleles in the promoter region of ACE2 gene were correlated with the occurrence of HCM (p0.05). Furthermore, it was found that the cardiac function and prognosis of HCM patients carrying genotype GG of polymorphism rs102312 were poorer than those of patients carrying genotype TT (p